THE IMPORTANCE OF ENGLISH IN PROFESSIONAL EDUCATION (Ustozlar uchun, 2026)
This study  examines  the  role  of  English  in  modern  education  and professional  development.  It  analyzes  how  proficiency  in  English  influences academic   performance,   career   opportunities,   international   collaboration,   and competitiveness in the labor market. The research utilized surveys, observations, and statistical analyses to assess the impact of English language skills on students and professionals.  Findings  indicate  that  individuals  with  strong  English  skills  have better   academic   outcomes,   greater   access   to   professional   opportunities,   and improved participation in global networks. The study highlights the importance of integrating  English  language  instruction  into  curricula  to  enhance  educational quality and professional mobility.